LDH-GO synergistically-reinforced flame-retardant polyolefin thermal management composite material, preparation method and application

By constructing LDH-GO hybrids and optimizing dispersion, the problems of flammability and high thermal conductivity of traditional polyolefin materials are solved, and the efficient flame retardant, thermal insulation and mechanical properties are improved, and it is suitable for electric vehicle battery thermal management and automotive interiors.

CN120157995APending Publication Date: 2025-06-17CHONGQING ORINKO TECH CO LTD CHINA
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510515582.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-23
Publication Date
2025-06-17

AI Technical Summary

Technical Problem

Traditional polyolefin materials are flammable and have high thermal conductivity, which is difficult to meet the needs of thermal management of electric vehicle batteries. At the same time, the existing flame retardant modification technology has problems of toxic gas release and material density increase.

Method used

LDH-GO hybrids are constructed through electrostatic self-assembly, and the dispersion is optimized with interface compatibilizers, so as to achieve synchronous improvement of gas-phase-condensation phase synergistic flame retardant, efficient heat insulation and mechanical properties.

Benefits of technology

It significantly improves the flame retardant and heat insulation capabilities of the material, reduces thermal conductivity and combustion smoke release, complies with environmental protection standards, and improves the mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005372468240000101
    Figure BDA0005372468240000101
Patent Text Reader

Abstract

The invention discloses an LDH-GO synergistically-reinforced flame-retardant polyolefin thermal management composite material, a preparation method and application, and belongs to the technical field of composite materials. The LDH-GO synergistically reinforced flame-retardant polyolefin thermal management composite material is prepared from the following raw materials in parts by mass: 80 to 95 parts of co-polypropylene, 5 to 20 parts of LDH-GO flame retardant, 2 to 5 parts of compatilizer, 0.1 to 0.3 part of antioxidant, 0.1 to 0.3 part of lubricant and 0.1 to 0.5 part of light stabilizer. Through a synergistic flame retardant mechanism of LDH and GO, the flame retardant property of the material is remarkably improved; the LDH is heated and decomposed to release H2O and CO2, the combustible gas is diluted, and the base body is cooled; gO forms a compact carbon layer during combustion to isolate heat and oxygen; and no halogen is added, the combustion smoke release amount is remarkably reduced, and the environmental protection property is superior to that of a traditional halogen flame retardant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite materials, and particularly relates to an LDH-GO synergistically enhanced flame-retardant polyolefin thermal management composite material, a preparation method and an application thereof. Background Art

[0002] With the development of the automotive industry towards lightweight, intelligent and environmentally friendly directions, the demand for high-performance polymer materials is becoming increasingly urgent. Polyolefins (such as polypropylene PP and polyethylene PE) are widely used in components such as automotive interiors, battery pack housings and wire harness sheaths due to their advantages of low cost, easy processing and chemical resistance. However, traditional polyolefin materials have significant defects: firstly, the limiting oxygen index (LOI) is usually lower than 18%, flammable and releasing a large amount of heat and toxic smoke during combustion, seriously threatening the safety of drivers and passengers; secondly, the thermal conductivity is relatively high (about 0.2-0.5 W / m·K), which is difficult to meet the demand for efficient heat insulation in electric vehicle battery thermal management. Existing flame-retardant modification technologies mostly rely on halogen-based flame retardants, although the LOI value can be increased to 25%-30%, but highly toxic gases such as dioxins are released during combustion, and high addition amounts (20%-30%) lead to an increase in material density and deterioration of mechanical properties, running counter to the goal of automotive lightweighting.

[0003] In recent years, inorganic nano-fillers (such as layered double hydroxide LDH and graphene oxide GO) have become a research hotspot due to their environmentally friendly and highly efficient flame-retardant properties. LDH decomposes upon heating to release water vapor and CO2, diluting combustible gases and cooling the matrix; GO forms a dense carbon layer during combustion, isolating oxygen and heat transfer. However, the limitations of single fillers are significant: LDH is prone to agglomeration due to strong interlayer electrostatic interactions, with poor dispersibility; although GO can enhance flame retardancy, excessive addition is likely to cause interfacial defects and reduce the toughness of the material. In addition, the non-polar surface of polyolefins has poor compatibility with polar nano-fillers, and it is difficult to achieve uniform dispersion by traditional melt blending processes, resulting in it being difficult to achieve both high flame-retardant efficiency and good mechanical properties.

[0004] To address the above problems, the present invention innovatively proposes an LDH-GO synergistically enhanced flame-retardant polyolefin composite material and a preparation method thereof. By electrostatic self-assembly, an LDH-GO hybrid is constructed, and the dispersibility is optimized by combining an interfacial compatibilizer, achieving synchronous improvement of gas-phase - condensed-phase synergistic flame retardancy, efficient heat insulation and mechanical properties. This technology breaks through the performance bottleneck of traditional flame-retardant systems, provides a material solution with safety, environmental friendliness and multifunctionality for automotive lightweighting and electrification, shows broad application prospects in fields such as battery thermal management and interior flame retardancy, and is expected to promote the iterative upgrade of new energy vehicle material technology. Summary of the Invention

[0005] Aiming at the deficiencies of the existing technology, the purpose of the present invention is to provide an LDH-GO synergistically enhanced flame-retardant polyolefin thermal management composite material, a preparation method and an application, which solve the problems in the existing technology.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] The LDH-GO synergistically enhanced flame-retardant polyolefin thermal management composite material comprises the following raw materials in parts by mass: 80-95 parts of copolymerized polypropylene, 5-20 parts of LDH-GO flame retardant, 2-5 parts of compatibilizer, 0.1-0.3 part of antioxidant, 0.1-0.3 part of lubricant and 0.1-0.5 part of light stabilizer.

[0008] Further, the preparation process of the LDH-GO flame retardant is as follows: Layered double hydroxide and graphene oxide are mixed in a mass ratio of 1:(1-2), and are ultrasonically dispersed in a 1-2 wt% surfactant deionized water solution, and an LDH-GO hybrid is formed by electrostatic adsorption; then freeze-drying is carried out to obtain the LDH-GO flame retardant.

[0009] Further, the surfactant is one of sodium dodecylbenzenesulfonate, polyvinylpyrrolidone, and polyvinyl alcohol.

[0010] Further, the conditions for the ultrasonic dispersion treatment are: power of 30-90 W, frequency of 10-20 Hz, time of 75-150 min, and temperature of 25-35 °C;

[0011] The specific conditions for the freeze-drying are a temperature of -20 °C to -50 °C, a pressure of 0.1-0.5 mbar, and a time of 48-72 h.

[0012] Further, the compatibilizer is one of maleic anhydride grafted polyolefin, ethylene-acrylic acid copolymer, and amino silane.

[0013] Further, the antioxidant is one of dipentaerythritol diisodecyl diphosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,4-bis((dodecylthio)methyl)-6-methylphenol, octadecyl 3,5-bis(1,1-dimethylethyl)-4-hydroxybenzenepropionate, tris(2,4-di-tert-butylphenyl) phosphite, and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propanoyl)hexanediamine.

[0014] Further, the light stabilizer is one of 5-chlorobenzotriazole, methyl 3-[3-(benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl]propionate, and bis(2,2,6,6-tetramethylpiperidinyl) sebacate.

[0015] Further, the lubricant is one of stearic acid, oleic acid, dodecanoic acid, tetradecanoic acid, polyethylene wax, and polypropylene wax.

[0016] The preparation method of the above-mentioned LDH-GO synergistically enhanced flame-retardant polyolefin thermal management composite material is characterized by comprising: putting copolymerized polypropylene, LDH-GO flame retardant, compatibilizer, antioxidant, lubricant, and light stabilizer into an extruder according to the said mass parts, and extruding and pelletizing to obtain the product.

[0017] The application of the above-mentioned LDH-GO synergistically enhanced flame-retardant polyolefin thermal management composite material as a raw material in manufacturing automotive interiors.

[0018] The beneficial effects of the present invention:

[0019] 1. Through the synergistic flame-retardant mechanism of LDH and GO, the present invention significantly improves the flame-retardant performance of the material. LDH decomposes upon heating to release H2O and CO2, diluting combustible gases and cooling the matrix (gas-phase flame retardancy); GO forms a dense carbon layer during combustion, isolating heat and oxygen (condensed-phase flame retardancy); experimental data shows that the limiting oxygen index (LOI) of 10% LDH-GO reaches 35.5%, and the combustion rate drops to 40 mm / min, meeting the B-level flame-retardant standard of GB 8410-2006 (combustion distance < 50 mm); the system has no halogen addition, and the combustion smoke release amount is significantly reduced, and the environmental protection performance is superior to traditional halogen-based flame retardants.

[0020] 2. The synergistic dispersion of LDH-GO significantly reduces the thermal conductivity of the material; the two-dimensional lamellae of GO extend the heat conduction path, and the uniform dispersion of LDH increases the interfacial thermal resistance. The synergistic effect enables the material to have high thermal insulation ability in scenarios such as battery module thermal insulation pads, and can effectively control the risk of thermal runaway.

[0021] 3. The present invention adopts a fully inorganic LDH-GO synergistic system, abandons halogen-based flame retardants, and has no dioxin release during combustion, meeting the RoHS regulations; the production cost is significantly reduced compared with traditional multi-layer composite processes, has the potential for industrialization, and can be widely applied in fields such as automotive interiors, battery thermal insulation, and electronic devices. Specific embodiments

[0022] Next, the technical solutions of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts fall within the protection scope of the present invention.

[0023] The LDH-GO synergistically enhanced flame-retardant polyolefin thermal management composite material comprises the following raw materials in parts by mass: 80-95 parts of copolymerized polypropylene, 5-20 parts of LDH-GO flame retardant, 2-5 parts of compatibilizer, 0.1-0.3 part of antioxidant, 0.1-0.3 part of lubricant, and 0.1-0.5 part of light stabilizer;

[0024] Among them, the preparation process of the LDH-GO flame retardant is as follows: Mix layered double hydroxide (LDH) and graphene oxide (GO) at a mass ratio of 1:(1-2), disperse them ultrasonically in a 1-2 wt% surfactant deionized aqueous solution, and form a stably dispersed LDH-GO hybrid through electrostatic adsorption. Subsequently, freeze-dry to obtain the LDH-GO flame retardant;

[0025] The surfactant is one of sodium dodecylbenzenesulfonate, polyvinylpyrrolidone, and polyvinyl alcohol; the conditions for the ultrasonic dispersion treatment are: power of 30-90 W, frequency of 10-20 Hz, time of 75-150 min, and temperature of 25-35 °C. The specific conditions for the freeze-drying are a temperature of -20 °C to -50 °C, a pressure of 0.1-0.5 mbar, and a time of 48-72 h.

[0026] The copolymerized polypropylene is one or a combination of more than one of Lanzhou Petrochemical copolymerized PP SP18I, EP508N, SK Sinopec-Korea copolymerized PP BX3800, and Zhongke copolymerized PP 640V.

[0027] The compatibilizer is one of maleic anhydride grafted polyolefin, ethylene-acrylic acid copolymer, and amino silane.

[0028] The antioxidant is one of dipentaerythritol diisodecyl diphosphite, pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,4-bis((dodecylthio)methyl)-6-methylphenol, octadecyl 3,5-bis(1,1-dimethylethyl)-4-hydroxybenzenepropionate, tris(2,4-di-tert-butylphenyl) phosphite, and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine.

[0029] The light stabilizer is one of 5-chlorobenzotriazole, methyl 3-[3-(benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl]propionate, and bis(2,2,6,6-tetramethylpiperidinol) ester.

[0030] The lubricant is one of stearic acid, oleic acid, dodecanoic acid, tetradecanoic acid, polyethylene wax, and polypropylene wax.

[0031] The technical solution of the present invention will be described below through the following examples;

[0032] Example 1

[0033] This example presents a polyolefin thermal management composite material, which includes the following raw materials in parts by weight: Lanzhou Petrochemical copolymerized PP EP508N: 45 parts, Lanzhou Petrochemical copolymerized SP179: 40 parts, LDH-GO flame retardant: 5 parts, compatibilizer (PE-g-MAH, Jiayirong Polymers (Shanghai) Co., Ltd.): 3 parts, antioxidant (BASF Germany Irganox 1010: 0.2 parts, Irganox168: 0.1 part), and light stabilizer (CYTEC USA ultraviolet absorber CYASORB UV-3808PP5): 0.1 part.

[0034] The preparation method of the polyolefin thermal management composite material in this example includes the following steps:

[0035] Step 1: Mix layered double hydroxide (LDH) and graphene oxide (GO) at a mass ratio of 1:1, and disperse them ultrasonically (power 30W, frequency 10Hz, time 75min, temperature 25°C) in a 1wt% sodium dodecylbenzenesulfonate aqueous solution to form a stably dispersed LDH-GO hybrid by electrostatic adsorption. Subsequently, freeze-dry (temperature -35°C, pressure 0.5mbr, time 48h) to obtain the flame retardant LDH-GO.

[0036] Step 2: Pre-blend the LDH-GO flame retardant, Lanzhou Petrochemical copolymerized PP EP508N, SP179, compatibilizer, antioxidant, and light stabilizer obtained in Step 1 in proportion, and then use a micro twin-screw extruder for blending and pelletizing to obtain a flame-retardant polyolefin thermal management composite material; among them, the feeding speed of the micro twin-screw extruder is 40rpm, the main machine speed is 650rpm, and the temperature control of each zone is set at 190°C, 200°C, 220°C, 220°C, 220°C, 220°C, 220°C, 210°C, 200°C, 200°C respectively.

[0037] In this example, the process of pre-blending is as follows: Using an SHR series high-speed mixer (kneader), first add PP pellets (EP508N, SP179) and compatibilizer, and mix at a low speed (400rpm) for 1 minute. Then add the LDH-GO flame retardant and mix at a medium speed (600rpm) for 2 minutes until preliminary dispersion. Finally, add small-dose additives such as antioxidant and light stabilizer, and mix at a high speed (1000rpm) for 6 minutes until uniform.

[0038] Example 2

[0039] The difference between this embodiment and Embodiment 1 is only that the polyolefin thermal management composite material comprises the following raw materials in parts by mass: Lanzhou Petrochemical copolymerized PP EP508N: 45 parts, Lanzhou Petrochemical copolymerized SP179: 32.5 parts, LDH-GO flame retardant: 12.5 parts, compatibilizer (PE-g-MAH, Jiayirong Polymers (Shanghai) Co., Ltd.): 4.5 parts, antioxidant (BASF Germany Irganox 1010: 0.2 part, Irganox 168: 0.1 part), light stabilizer (CYTEC (USA) ultraviolet absorber CYASORB UV-3808PP5): 0.3 part).

[0040] Among them, the preparation steps of the polyolefin thermal management composite material are the same as those in Embodiment 2.

[0041] Embodiment 3

[0042] This embodiment provides a polyolefin thermal management composite material, which comprises the following component raw materials in parts by weight: Lanzhou Petrochemical copolymerized PP EP508N: 40 parts, Lanzhou Petrochemical copolymerized SP179: 40 parts, LDH-GO flame retardant: 20 parts, compatibilizer (PE-g-MAH, Jiayirong Polymers (Shanghai) Co., Ltd.): 6 parts, antioxidant (BASF Germany Irganox 1010: 0.2 part, Irganox168: 0.1 part), light stabilizer (CYTEC (USA) ultraviolet absorber CYASORB UV-3808PP5): 0.5 part).

[0043] The preparation steps of the polyolefin thermal management composite material are as follows:

[0044] Step 1: Mix layered double hydroxide (LDH) and graphene oxide (GO) at a mass ratio of 1:2, and disperse them in a 2Wt% sodium dodecylbenzenesulfonate aqueous solution by ultrasonic dispersion (power 90W, frequency 20Hz, time 150min, temperature 35°C) to form a stably dispersed LDH-GO hybrid by electrostatic adsorption. Subsequently, freeze-dry (temperature -50°C, pressure 0.1mbr, time 72h) to obtain the flame retardant LDH-GO.

[0045] Step 2: Pre-blend the flame retardant, Lanzhou Petrochemical copolymerized PP EP508N, SP179, compatibilizer, antioxidant, and light stabilizer obtained in Step 1 in proportion, and then use a micro twin-screw extruder for blending and granulation to obtain the flame-retardant polyolefin thermal management composite material. Among them, the feeding speed of the micro twin-screw extruder is 40rpm, the main machine speed is 650rpm, and the temperature control of each zone is set at 190°C, 200°C, 220°C, 220°C, 220°C, 220°C, 220°C, 210°C, 200°C, 200°C respectively.

[0046] Comparative Example 1

[0047] This comparative example presents a flame-retardant polyolefin thermal management composite material, which comprises the following component raw materials in parts by weight: Lanzhou Petrochemical copolymerized PP EP508N: 45 parts, Lanzhou Petrochemical copolymerized SP179: 40 parts, LDH: 5 parts, compatibilizer (PE-g-MAH, Jiayirong Polymers (Shanghai) Co., Ltd.): 3 parts, antioxidant (BASF Germany Irganox 1010: 0.2 parts, Irganox 168: 0.1 part), light stabilizer (CYTEC (USA) ultraviolet absorber CYASORB UV-3808PP5): 0.1 part.

[0048] The preparation method of the flame-retardant polyolefin thermal management composite material in this comparative example comprises the following steps:

[0049] Pre-mix Lanzhou Petrochemical copolymerized PP, LDH, compatibilizer, antioxidant, and light stabilizer in proportion, and then use a micro twin-screw extruder for blending and pelletizing to obtain the polyolefin thermal management composite material. Among them, the feeding speed of the micro twin-screw extruder is 40 rpm, the main machine speed is 650 rpm, and the temperature control of each zone is set at 190 °C, 200 °C, 220 °C, 220 °C, 220 °C, 220 °C, 220 °C, 210 °C, 200 °C, 200 °C respectively.

[0050] Comparative Example 2

[0051] This comparative example presents a flame-retardant polyolefin thermal management composite material. The only difference from Comparative Example 1 is that LDH in the raw materials is replaced by GO. It comprises the following component raw materials in parts by weight: Lanzhou Petrochemical copolymerized PP EP508N: 45 parts, Lanzhou Petrochemical copolymerized SP179: 40 parts, GO: 5 parts, compatibilizer (PE-g-MAH, Jiayirong Polymers (Shanghai) Co., Ltd.): 3 parts, antioxidant (BASF Germany Irganox 1010: 0.2 parts, Irganox 168: 0.1 part), light stabilizer (CYTEC (USA) ultraviolet absorber CYASORB UV-3808PP5): 0.1 part.

[0052] The preparation method of the flame-retardant polyolefin thermal management composite material in this comparative example comprises the following steps:

[0053] Pre-mix Lanzhou Petrochemical copolymerized PP, GO, compatibilizer, antioxidant, and light stabilizer in proportion, and then use a micro twin-screw extruder for blending and pelletizing to obtain the polyolefin thermal management composite material. Among them, the feeding speed of the micro twin-screw extruder is 40 rpm, the main machine speed is 650 rpm, and the temperature control of each zone is set at 190 °C, 200 °C, 220 °C, 220 °C, 220 °C, 220 °C, 220 °C, 210 °C, 200 °C, 200 °C respectively.

[0054] Experimental Test

[0055] After drying the polyolefin thermal management composites prepared in Examples 1-3 and Comparative Examples 1-2, a spline and a combustion plate (flame retardancy test: 356 mm * 100 mm * 2.5 mm) were prepared using an injection molding machine. The injection temperature was 220 °C, the mold temperature was 50 °C, and the holding pressure time was 6 s. Performance tests were carried out on the prepared splines. The specific test methods for the basic physical properties of the flame-retardant polyolefin thermal management composites are as follows:

[0056] 1) Density: According to the requirements of Method A (immersion method) in GB / T 1033.1, experiments were carried out using a sample block with dimensions of at least 10 mm × 10 mm × 4 mm;

[0057] 2) Ash content: According to GB / T 9345.1, Method A (direct calcination method), experiments were carried out at a temperature of 600 ± 25 °C;

[0058] 3) Melt flow rate (MFR): Experiments were carried out according to GB / T 3682 at an experimental temperature of 230 °C and a load of 2.16 Kg;

[0059] 4) Tensile strength: Experiments were carried out according to GB / T 1040.1 and GB / T 1040.2 using a 1A type injection molded spline with an experimental speed of 50 mm / min;

[0060] 5) Flexural strength and flexural modulus: Experiments were carried out according to GB / T 9341 with a spline size of 80 mm × 10 mm × (4.0 ± 0.2) mm, an experimental speed of 2 mm / min, and a support span of 64 mm;

[0061] 6) Izod notched impact strength (23 °C): Experiments were carried out according to GB / T 1843 with a spline size of 80 mm × 10 mm × (4.0 ± 0.2) mm, a Type A notch, and the notch was machined mechanically;

[0062] 7) Limiting oxygen index: Experiments were carried out according to GB / T 2406 with a spline size of 100 mm × 10 mm × 4 mm;

[0063] 8) Flame retardancy test: Experiments were carried out according to GB 8410-2006. Specimen: 356 mm * 100 mm * 2.5 mm, flame height: 38 mm, ignition time: 15 s. Pretreatment: Pretreated for 24 hours in an environment of (23 ± 2) °C / (50 ± 5) % RH. Among them, the judgment results are:

[0064] A - The specimen was not ignited or extinguished before reaching the first marking line

[0065] B - The flame of the specimen extinguished within 60 s of timing and the burning distance was less than 50 mm

[0066] Specimen C extinguishes itself between the two marking lines and does not meet the requirements of Class B specimens

[0067] D - Burns normally to the second marking line

[0068] E - The specimen burns to the first marking line within 15 s after being ignited by the flame

[0069] 9) Thermal conductivity test: In this study, a Hot Disk thermal constant analyzer (TPS2500S) was used to measure the thermal conductivity of the examples and comparative examples by the transient plane heat source method. The probe model used for measurement was 5465F1, and the radius of the probe used for measurement was 3.189 mm.

[0070] The test results are shown in Table 1

[0071] Table 1 Performance test results

[0072]

[0073] According to the experimental data, the LDH / GO synergistically enhanced polyolefin composites showed significant optimization in mechanical properties, thermal conductivity, and flame retardancy. As the addition amount of LDH / GO increased (from Example 1 to Example 3), the material density increased from 0.945 g / cm 3 to 1.051 g / cm 3 , and the ash content increased from 4.9% to 20.3%, indicating an increase in the proportion of inorganic fillers. The melt index decreased slightly (from 25.3 to 23.8 g / 10 min), but had a limited impact on the processing performance. In terms of mechanical properties, the tensile strength decreased slightly (from 21.8 to 20.8 MPa), but the flexural strength and modulus increased significantly (the flexural strength increased from 22.7 MPa to 28.9 MPa, and the modulus increased from 1390 MPa to 2059 MPa). The Izod notched impact strength increased from 4.6 kJ / m 2 to 5.3 kJ / m 2 , indicating that the fillers enhanced the rigidity and toughness through interface strengthening. In terms of flame retardant performance, the limiting oxygen index (LOI) increased from 32.0% to 38.0%, and the burning rate decreased from 60.5 mm / min (Class C) to 42.6 mm / min (Class B), indicating that the synergistic effect of the gas-phase flame retardancy of LDH and the carbon layer barrier of GO significantly inhibited combustion. The thermal conductivity decreased from 0.16 W / m·K to 0.10 W / m·K, which is better than that of pure PP (0.3 W / m·K), proving that the high aspect ratio structure of GO effectively extended the heat conduction path. In summary, the LDH / GO synergistic system achieved a balance of flame retardancy, heat insulation, and mechanical properties at a low addition amount (10%), and is particularly suitable for scenarios such as automotive interiors that require both safety and lightweight.

[0074] In the description of this specification, the descriptions referring to terms such as "one embodiment", "example", "specific example", etc. mean that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0075] The above has shown and described the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and what is described in the above embodiments and the specification only illustrates the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention will have various changes and improvements, and these changes and improvements all fall within the scope of the present invention claimed.

Claims

1. LDH-GO synergistically reinforced flame retardant polyolefin thermal management composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 80-95 parts of copolymerized polypropylene, 5-20 parts of LDH-GO flame retardant, 2-5 parts of compatibilizer, 0.1-0.3 parts of antioxidant, 0.1-0.3 parts of lubricant and 0.1-0.5 parts of light stabilizer.

2. The LDH-GO synergistically reinforced flame-retardant polyolefin thermal management composite material according to claim 1, characterized in that: The preparation process of LDH-GO flame retardant is as follows: layered double hydroxide and graphene oxide are mixed in a mass ratio of 1:(1-2), dispersed in a 1-2wt% surfactant deionized water solution by ultrasonic, and an LDH-GO hybrid is formed by electrostatic adsorption; then freeze-dried to obtain the LDH-GO flame retardant.

3. The LDH-GO synergistically reinforced flame-retardant polyolefin thermal management composite material according to claim 2, characterized in that: The surfactant is one of sodium dodecylbenzene sulfonate, polyvinyl pyrrolidone and polyvinyl alcohol.

4. The LDH-GO synergistically reinforced flame-retardant polyolefin thermal management composite material according to claim 2, characterized in that: The conditions of the ultrasonic dispersion treatment are: power 30-90W, frequency 10-20Hz, time 75-150min, temperature 25-35°C; The specific conditions of freeze drying are a temperature of -20°C to -50°C, a pressure of 0.1-0.5 mbar, and a time of 48-72 hours.

5. The LDH-GO synergistically reinforced flame-retardant polyolefin thermal management composite material according to claim 1, characterized in that: The compatibilizer is one of maleic anhydride grafted polyolefin, ethylene-acrylic acid copolymer and aminosilane.

6. The LDH-GO synergistically reinforced flame-retardant polyolefin thermal management composite material according to claim 1, characterized in that: The antioxidant is one of pentaerythritol diisodecyl diphosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,4-bis((dodecylthio)methyl)-6-methylphenol, octadecyl-3,5-bis(1,1-dimethylethyl)-4-hydroxyphenylpropionate, tris(2,4-di-tert-butylphenyl) phosphite, and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine.

7. The LDH-GO synergistically reinforced flame-retardant polyolefin thermal management composite material according to claim 1, characterized in that: The light stabilizer is one of 5-chlorobenzotriazole, 3-[3-(benzotriazole-2-yl)-5-tert-butyl-4-hydroxyphenyl]propionic acid methyl ester, and bis-2,2,6,6-tetramethylpiperidinol ester.

8. The LDH-GO synergistically reinforced flame-retardant polyolefin thermal management composite material according to claim 1, characterized in that: The lubricant is one of stearic acid, oleic acid, dodecanoic acid, tetradecanoic acid, polyethylene wax and polypropylene wax.

9. The method for preparing the LDH-GO synergistically reinforced flame-retardant polyolefin thermal management composite material according to any one of claims 1 to 8, characterized in that: include: The copolymerized polypropylene, LDH-GO flame retardant, compatibilizer, antioxidant, lubricant and light stabilizer are put into an extruder according to the mass fractions, and extruded into granules to obtain the product.

10. Use of the LDH-GO synergistically reinforced flame-retardant polyolefin thermal management composite material according to any one of claims 1 to 8 as a raw material in the manufacture of automobile interiors.

Citation Information

Cited By

  • Cable coating material with high flame retardance and preparation method thereof

    CN121064550A

  • A high flame-retardant cable sheathing material and its preparation method

    CN121064550B